Iridescent chiral nematic papers based on cellulose nanocrystals with multiple optical responses for patterned coatings. (1st August 2022) - Zhao, Haodong; Dai, Xiaonan; Yuan, Zaiwu; Li, Guihua; Fu, Yingjuan; Qin, Menghua
Abstract: Chiral nematic papers (CNPs) with mesopores structure based on cellulose nanocrystals (CNCs) were fabricated successfully via a swelling and freeze-drying method. The order of the original chiral nematic cellulose nanocrystals film was preserved in CNPs, which was proved by scanning electron microscopy (SEM), polarized optical microscopy (POM) measurements and circular dichroism (CD) spectra. The CNPs exhibited excellent optical responsive properties to different solvents. Inspired by this feature, a colorable ink containing amounts of gel particles was prepared by pulverizing CNPs/water mixture into a suspension. Patterns written in suspension ink with various colors can be formed when soaked with different solvents. Moreover, CNPs displayed an irreversible color response to compression. Additionally, the hydrophilicity of CNPs was tuned by polyethyleneimine. Modified CNPs exhibited different colors under the identical solvent environment when compared to the original one. Aqueous PEI can be used as an ink to depict responsive photonic patterns on CNPs. Graphical abstract: Iridescent chiral nematic papers (CNPs) with mesopores structure exhibit excellent optical responsive properties to mixed solvents. Modified CNPs with polyethylene imine (PEI) display different colors under the identical solvent environment when compared to the original one. Aqueous PEI can be used as an ink to depict responsive photonic patterns on CNPs. Unlabelled Image